Longitudinal Evidence for Simultaneous Bilingual Language Development With Shifting Language Dominance, and How to Explain It. (15th June 2020) - Oppenheim, Gary M.; Griffin, Zenzi; Peña, Elizabeth D.; Bedore, Lisa M.
Abstract: Theories of how language works have shifted from rule‐like competence accounts to more skill‐like incremental learning accounts. Under these, people acquire language incrementally, through practice, and may even lose it incrementally as they acquire competing mappings. Incremental learning implies that (1) a bilingual's abilities in their languages should depend on how much they practice each (not merely age of acquisition), and (2) using a L2 more could cause a bilingual to gradually "unlearn" their L1. Using timed picture naming and vocabulary measures, we tracked 139 children for several years as they transitioned from mostly‐Spanish homes to mostly‐English schools. Following their increased English use, many became more proficient in English than Spanish around the third grade, demonstrating continual learning. But their Spanish also improved, showing that L1‐attrition is not inevitable. Incremental learning explains both co‐improvement and L1‐attrition as consequences of experience‐driven learning: improvement from continuing L1 use can offset competitive unlearning. Abstract :